Evaluating the quality of pole concrete production through the integration of Six Sigma and Kaizen - Darmawan, Armin; Bahri, Syamsul; Fansuri, Ilham; Tahir, Nurfaidah (Universitas Sultan Ageng Tirtayasa, 2024)
Competitive industries can thrive by emphasizing quality, which is essential for a company's growth. This study examines the quality control of a concrete manufacturer's precast concrete electric pole products. The research aims to detect product defects and assess quality levels using the sigma level, while also suggesting improvements. However, some manufactured products still exhibit defects. To address this, Six Sigma is employed to enhance quality. The Six Sigma methodology follows five steps: Define, Measure, Analyze, Improve, and Control (DMAIC). In the Define stage, issues such as cracks, pole alignment, fin breadth, skin stickiness, lumps, ovals, and through holes are identified. According to the Pareto diagram, defects related to cracks, fin width, and skin stickiness have dominated the measurement stage over the past seven years. In the Analyze stage, factors such as insufficient supervision, failure to maintain aging machines and equipment, and uncontrolled raw materials are identified as causes. During the Improve stage, Kaizen’s 5W+1H approach is used to propose improvements. By adopting these improvement recommendations, the company can significantly reduce defects.